2020
DOI: 10.1002/cite.202000081
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Innovative Technologies in Liquid‐Liquid Extraction Regarding Flexibility

Abstract: As a result of increasing market volatility and product diversification the technology requirements will change in the future. Flexibility needs to be increased, enabling a large operating window while maintaining intensive mass and energy transfer and resource‐efficiency. A promising approach is using innovative small‐scale technologies. To assess flexibility, the technologies must be characterized in a wide range of operating parameters and physical properties. Therefore, research work on innovative technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Almost all analytical measurements require some form of sample preparation which may include simple filtration of the sample, extraction of an analyte from quite complex sample matrices, or concentration of analyte(s) for detection [1, 2]. Liquid‐liquid extraction [3–5] and SPE [6, 7] are well‐known methods used to enrich sample concentrations between 10 and 1000 times [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all analytical measurements require some form of sample preparation which may include simple filtration of the sample, extraction of an analyte from quite complex sample matrices, or concentration of analyte(s) for detection [1, 2]. Liquid‐liquid extraction [3–5] and SPE [6, 7] are well‐known methods used to enrich sample concentrations between 10 and 1000 times [8].…”
Section: Introductionmentioning
confidence: 99%
“…complex sample matrices, or concentration of analyte(s) for detection [1,2]. Liquid-liquid extraction [3][4][5] and SPE [6,7] are well-known methods used to enrich sample concentrations between 10 and 1000 times [8].…”
Section: Introductionmentioning
confidence: 99%
“…69,98 Flexibilities in the purification of bio-based products have been investigated for sedimentation, thermal drying, membrane separation, distillation, cryogenic separation, and absorption processes. A comprehensive review of flexibility options in liquid-liquid extraction was conducted by Polyakova et al, 99 The possible FOL of investigated process steps that are found in biofuel production and can be operated flexibly are summarized in Figure 6.…”
Section: Refining Processesmentioning
confidence: 99%
“…Liquid–liquid extraction processes are widely used in different fields of fine chemistry, pharmaceutical production, and so forth. The stirred solvent extraction column operated in the countercurrent mode plays an important role in today’s chemical industry …”
Section: Introductionmentioning
confidence: 99%